Application of light-emitting diodes (LEDs) in cultivation of phototrophic microalgae: current state and perspectives - Becker, Anna; Glemser, M.; Heining, Martin; Schmidt, J.; Becker, A.; Garbe, Daniel; Buchholz, Rainer; Brueck, T. (Applied Microbiology and Biotechnology, 2016)
The quality and regulation of the incident light is crucial in microalgae cultivation processes. Depending on wavelength, spectrum, and intensity, growth characteristics and biochemical composition of these organisms vary. With mainly fluorescent lamps (FL) used previously for illumination, such variabilities could not be studied adequately due to their broad emission spectrum. In contrast, light-emitting diodes (LEDs) emit a very narrow wavelength band and enable flexible photobioreactor designs due to their small size. This review provides a condensed overview on the application of LEDs in microalgal cultivation processes. It summarizes the current availability and applicability of LED technologies as an illumination source for research-focused photobioreactor systems. A particular focus is the use of narrow-wavelength LEDs to address fundamental as well as applied aspects of light color on algae biomass and value-added compound formation. In this respect, the application of internal and external illumination systems is reviewed together with trends in the industrial use of LED systems to intensify algae process efficiency.
Keywords: LED; Light-emitting diodes; Microalgae; Photobioreactor; Wavelengths